Integration of aquifer resistivity and hydrogeochemical data for groundwater quality assessment in a basement complex terrain of Osogbo metropolis, Southwest Nigeria - BAYOWA, Oyelowo Gabriel; OGUNGBESAN, Gbenga Olakunle; ELUWOLE, Akinola Bolaji; AKINLOYE, Kehinde Francis; ADELERE, Isaiah Oluwadara; ABUBAKAR, Hussain Olanrewaju; BABATUNDE, Segun Adebayo (Contributions to Geophysics and Geodesy, 2025)
In this paper, one hundred and nine vertical electrical sounding data were acquired and quantitatively interpreted to delineate the subsurface sequence and determine the geoelectric parameters. One hundred and eighteen shallow wells with measured depths to the water table were sampled and thirty-five ground-water samples were analysed for physicochemical parameters, in a view to assessing the groundwater quality in Osogbo metropolis, Southwest Nigeria. The delineated subsurface layers included the topsoil/laterite, weathered layer; partly weathered/fractured basement and the basal fresh basement with respective resistivities and thicknesses: 13 – 4727 Ωm and 0.2 – 8.9 m; 70 – 641 Ωm and 0.8 – 32.0 m; 18 – 826 Ωm and 1.8 – 27.9; and 349 – ∞ Ωm and ∞ m. The main aquifer unit identified was the weathered layer which was classified into ≤ 100 Ωm (low), 101 – 350 Ωm (moderate) and 350 – 750 Ωm (high) resistivity zones. Depths to the water table ranged from 3.1 – 40.7 m. The analysed physicochemical parameters included the pH (5.31 – 7.33), Electrical Conductivity (EC) (90 – 1709 μs/m); Total dissolved Solid (TDS) (89 – 1227 mg/L); Ca2+ (1.9 – 93 mg/L); Na+ (9.2 – 349 mg/L); K+ (0.8 – 60 mg/L); and NO3− (0.9 – 4.9 mg/L). The central district of the study area with relatively shallow water table < 12 m) and cluster of ancient waste dumpsites fell within the low resistivity zone having physicochemical characteristics of high TDS (623 – 1227 mg/L) and EC (903 – 1709 μs/m) and elevated concentrations of Na+ (120 – 349 mg/L), Ca2+ (48 – 93 mg/L) and K+ (25 – 60 mg/L) relative to WHO (2022) and SON (2015) thresholds for potable water and adjudged a poor groundwater quality zone. The pollutant is suspected to be leachates from waste dumpsites and pit latrines.